Tortilla Flat - Steinbeck, John, 1902-1968. (New York, N.Y. : Penguin Books, 1986)
Above the town of Monterey on the California coast lies the shabby district of Tortilla Flat where Danny and his colorful group of friends live and where their revels recall the exploits of King Arthur's knights.
Booklist.
Library Journal.
Wilson's Fiction.
Young Adult
Keywords: Hispanic Americans -- Fiction; Poverty -- California -- Monterey -- Fiction; Hispanic Americans -- Fiction; Poverty -- Fiction; Monterey (Calif.) -- Fiction; Monterey (Calif.) -- Fiction